Management of Persistent Pruritus and Lichenoid Reaction Secondary to Nivolumab With Narrowband Ultraviolet B Phototherapy - Donaldson, Marie; Owen, Joshua L.; Chae, Young K.; Choi, Jennifer N. (Frontiers in Oncology, 2018)
Immune checkpoint inhibitors targeting the programmed cell death receptor 1 (PD-1) are being increasingly utilized in the treatment of a variety of malignancies. The most common adverse events with anti-PD-1 therapy are cutaneous toxicities. We report the case of a 68-year-old man with stage IV non-small cell lung cancer treated with nivolumab who developed a severe lichenoid eruption that responded to systemic steroids, but was recalcitrant to steroid taper. The use of narrowband ultraviolet B phototherapy allowed for full resolution of the rash, cessation of systemic steroids, and continuation of nivolumab.